Currículo e projetos sob o olhar interdisciplinar: um estudo de caso na Escola Municipal de Tempo Integral Vinicius de Moraes - Silva, Clebson Gomes da (Universidade Federal do Tocantins, 2021)
The dissertation brings to the discussion issues related to the Curriculum and School Projects seen from an interdisciplinary perspective. The main objective was to understand the school curriculum from school projects, in full-time school, from the perspective of interdisciplinarity. Authors such as Fazenda (2004; 2006), Japiassu (1976), Moraes (1997; 2008), among others, were sought for some of the main sources of discussion and analysis of the research problem that is outlined from a study of case, of qualitative approach in the Municipal School of Integral Time Vinícius de Moraes, located in the center of Palmas, Tocantins. The survey of data and information was developed from in loco observations, institutional documents and through a semistructured interview guide, applied to 05 professionals working in the field school. It was identified with the study that, although the use of the term interdisciplinarity in school is common, its conceptualization and understanding may present difficulties in understanding and different interpretations, positions and paths in the development of the curriculum and school projects. However, the research identified methodological and epistemological elements with interdisciplinary possibilities and openings. The construction of an interdisciplinary work can lead to ways that contribute to the integration of the school, through its curriculum and through its projects, as well as helping to understand how this epistemology develops in the daily life of the school.